Pulsed Iron Line Emission from the First Galactic Ultraluminous X-Ray Pulsar Swift J0243.6+6124 - Y. X. Xiao; Y. J. Xu; M. Y. Ge; F. J. Lu; S. N. Zhang; S. Zhang; L. Tao; J. L. Qu; P. J. Wang; L. D. Kong; Y. L. Tuo; Y. You; et al. (The Astrophysical Journal, 2024)
We report the phase-resolved spectral results of the first Galactic pulsating ultraluminous X-ray source (PULX) Swift J0243.6+6124, modeling its 2017–2018 outburst peak using data collected by the Hard X-ray Modulation Telescope (Insight-HXMT). The broad energy coverage of Insight-HXMT allows us to obtain a more accurate spectral continuum to reduce the coupling of broad iron line profiles with other components. We use three different continuum spectrum models but obtain similar iron line results. For the first time, we detect the pulse characteristics of the broad iron line in a PULX. The variation in the width and intensity of this iron line with σ ∼ 1.2–1.5 keV has a phase offset of about 0.25 from the pulse phase. We suggest that the uneven irradiation of the thick inner disk by the accretion column produces the modulated variation of the broad iron line. In addition, the nonpulsed narrow line is suggested to come from the outer disk region.